Book of Stunting Risk Detection and Monitoring Health (DRSMK) and Stunting Prevention Behavior in Children the First 1000 Days of Life - Anita, A; Purwati, P; Desmarnita, Ulty (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Riskesdas (2018) stated that the stunting or the short stature in children due to chronic malnutrition was at 30.8%, severe malnutrition and nutritional deficiency were at 17.7%. This figure is still far from the World Health Organization (WHO) target of 20%. This means that stunting for toddlers in Indonesia is still above the tolerance limits imposed by the World Health Organization. The purpose of this study was to determine the effects of the use of the book of Stunting Risk Detection and Health Monitor (DRSMK) by Posyandu cadres on the behaviour of Stunting prevention in pregnant women and parenting patterns on children care in the first 1000 days of life in South Lampung Regency. The research output was a cadre manual book in the effort to prevent stunting from pregnancy to the age of 1000 days of life. This research used quantitative research, quasi-experimental analytic research design. The study was conducted in 8 villages in Lampung Selatan Regency, Lampung Province. The number of samples was 120, the treatment group was 60 and the control was 60 respondents. The treatment group was given health education and trained to use the DSRMK Book by the health cadre for 3 months, then measured behaviour and parenting pattern in preventing stunting. In the control group was given counselling according to the puskesmas SOP. The results showed that 1) there was an influence on the use of DRSMK books by Posyandu cadres to prevent maternal stunting through ANC examination. 2) There was an influence on the use of DRSMK books by Posyandu cadres on the prevention of maternal stunting behaviour during pregnancy, 3) there was the influence on the use of DRSMK books by posyandu cadres on parenting patterns in preventing stunting. The DRSMK book is easy to use by health cadres in an effort to prevent and detect stunting from pregnancy to 24 months old.Abstrak: Riskesdas (2018) menyatakan proporsi stunting atau balita pendek karena kurang gizi kronik sejumlah 30,8%, gizi buruk dan gizi kurang 17,7%. Angka ini masih jauh dari target Badan Kesehatan Dunia (WHO) yakni 20%.  Hal ini memberi arti stunting Balita di Indonesia saat ini masih di atas batas toleransi yang ditetapkan oleh Badan Kesehatan Dunia. Tujuan penelitian untuk mengetahui Pengaruh Penggunaan Buku Deteksi Risiko Stunting dan Monitor Kesehatan (DRSMK) oleh Kader Posyandu terhadap Perilaku pencegahan Stunting pada ibu hamil dan pola asuh pada perawatan anak 1000 hari pertama kehidupan di Kabupaten Lampung Selatan. Luaran penelitian adalah buku panduan kader dalam upaya pencegahan stunting mulai dari masa kehamilan sampai usia 1000 hari kehidupan. Jenis penelitian kuantitatif, rancangan penelitian analitik quasi eksperimen. Penelitian dilakukan di 8 desa di Kabupaten Lampung selatan Provinsi Lampung. Jumlah sampel 120, kelompok perlakuan 60 dan kontrol 60 responden. Kelompok perlakuan diberikan pendidikan kesehatan dan dilatih menggunakan Buku DSRMK oleh kader kesehatan selama 3 bulan, selanjutnya diukur perilaku dan pola asuh dalam mencegah terjadinya stunting. Pada kelompok kontrol diberikan penyuluhan sesuai SOP puskesmas. Hasil penelitian menunjukkan 1) ada pengaruh penggunaan buku DRSMK oleh kader Posyandu terhadap perilaku pencegahan stunting ibu melalui pemeriksaan ANC. 2) ada pengaruh penggunaan buku DRSMK oleh kader Posyandu terhadap perilaku pencegahan stunting ibu masa kehamilan, 3) ada pengaruh penggunaan buku DRSMK oleh kader posyandu terhadap pola asuh anak dalam pencegahan stunting. Buku DRSMK mudah digunakan oleh kader kesehatan dalam upaya pencegahan dan deteksi stunting mulai kehamilan sampai anak berusia 24 bulan.